(untitled) - Mensah, Kuassi (Amsterdam,London, 2006)
All you need to know to use Java and Webservice to manage the Oracle Database 10g R2
Keywords: Database management,Java (Computer program language),Web services,Quản trị cơ sở dữ liệu,Java (Ngôn ngữ lập trình máy tính),Dịch vụ mạng